‘They Kill Us Trans Women’: Migration, informal labour, and sex work among trans Venezuelan asylum seekers and undocumented migrants in Brazil during COVID-19 - Su, Yvonne; Valiquette, Tyler (Anti-Trafficking Review, 2022)
This short article contributes to the growing scholarship on the complex ways sexual orientation and gender identity impact people’s experiences of migration, informal labour, and sex work. Drawing on surveys and interviews with twelve trans Venezuelan asylum seekers and undocumented migrants in Brazil and six key informant interviews with sex workers, trans activists, and humanitarian and NGO staff, this short article asks: How has COVID-19 affected the livelihoods of trans Venezuelan asylum seekers and undocumented migrants?